TERAPI ENDOVASKULAR ANEURISMA KAROTIS KAVERNOSA DENGAN PIPELINE FLEX EMBOLIZATION DEVICE PENGAMATAN 1 TAHUN - Muhammad Yunus Amran,*,** Seung Pil Ban,** Ashari Bahar,* O-Ki Kwon** (NEURONA, 2019)
INTRACRANIAL ANEURYSMS ARE USUALLY DETECTED ACCIDENTALLY THROUGH NEUROIMAGING HOWEVER A LARGE INTRACRANIAL ANEURYSM 1524MM IS MORE LIKELY TO MANIFEST CLINICALLY DUE TO ITS MASS EFFECT ANEURYSMS IN THE CAVERNOUS SEGMENT OF CAROTID ARTERY GENERALLY EXHIBIT OCCULOMOTOR NERVE PALSY HEADACHE AND DIZZINESS THE SELECTION OF ENDOVASCULAR THERAPY DEPENDS ON THE TYPE AND MORPHOLOGY OF THE ANEURYSM